STAKEHOLDER PRESSURE AND THE QUALITY OF SUSTAINABILITY REPORT: EVIDENCE FROM INDONESIA - Lulu, Claudia Leonirda (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2021)
This study aims to determine the effect of environmental pressure, consumer pressure, shareholder pressure, employee pressure, government pressure and creditor pressure on the quality of sustainability reports. The control variables of this study are profitability and company size. The sampling technique used is a purposive sampling method with the number of samples obtained as many as 69 non-financial sector companies listed in Indonesia Stock Exchange for the period of 2016-2018. A multiple linear regression method was used. The results of this study indicate that environmental pressure and consumer pressure have a positive effect on the quality of sustainability reports, while shareholder pressure, employee pressure, government pressure and creditor pressure do not affect the quality of sustainability reports. Profitability and company size as control variables in this study do not affect the quality of sustainability reports. Keywords: stakeholder pressure, profitability, company size, quality of sustainability reports